Upaya Meningkatkan Hasil Belajar IPA dengan Menggunakan Media Gambar pada Siswa Kelas V SD GMIH Desa Towara Kecamatan Morotai Jaya Kabupaten Pulau Morotai - Risky Richlos Sarapung; Rustam Baba (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pasifik Morotai, 2022)
This research was conducted with the aim of improving student learning outcomes by using picture media in science subjects with Plant Parts material, in fifth grade students of SD GMIH Towara, Morotai Jaya District, Morotai Island Regency. The research model used in this study is a classroom action research (CAR) model which was held for fifth grade students at SD GMIH Towara, with a total of 24 students consisting of 6 girls and 18 boys. Meanwhile, the teacher who helped become an observer during this research was the homeroom teacher of class V SD GMIH Towara. The results of the research in the first cycle, students who completed were 14 people (58%) of the total (24 students), while 10 students (41%) had not succeeded. In the second cycle there was an increase in learning outcomes by (25%), so that students who were successful in the second cycle were 20 students (83%) and those who had not succeeded were 4 students (17%). Teaching and learning activities using Picture Media can improve science learning outcomes with the material